(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
Two new species of the genus Lithothamnion and one of Lithophyllum were discovered in the burdigalian section of Bric Cardinelle (Visone Formation, Tertiary Piedmont Basin). The holotypes are present in rhodoliths coming from oncolitic rudstone or calciruditic bodies. The new species are characterised by morphological features and dimensions of cells that are clearly different from those of the other recorded species of Lithothamnion and Lithophyllum.